Narratives of childhood in regional Western Australian towns: A trajectory of hope and collective wisdom for landmark reforms - Giamminuti, S.; Tye, M.; Buckley, A.; Merewether, Jane; Kuzich, S. (2015)
The early childhood education and care reforms in Australia have been heralded as a cause for celebration, greatly anticipated by a sector that has lamented its invisibility. Drawing on qualitative data from a study of three towns in the south-west of Western Australia, this article aims to provoke reflection on where we stand with the celebrated aim of putting young children at the centre of the vision for Australia. The South-West Early Childhood Project investigated how childhood is constructed and how communities welcome families and young children. The study identified several themes: narratives of invisibility/ visibility; narratives of sitting still/being active; and narratives of conformity/diversity. The article foregrounds the acclaimed experience of the city of Reggio Emilia (Italy) and extends an invitation to communities in Australia to position themselves on a trajectory of hope by harnessing collective wisdom in support of landmark early childhood reforms.